PEMBAHARUAN KEBIJAKAN HUKUM ASSET RECOVERY: ANTARA IUS CONSTITUTUM DAN IUS CONSTITUENDUM - Pakpahan, Rudy Hendra; Firdaus, Aras (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2019)
AbstractCorruption is not only detriment of state finances but also a violation of the social and economic rights of the people. The seizure and return of assets resulting from corruption have not yet be carried out comprehensively and effectively under the law in disclosing corruption. In addition, seizing and returning assets resulting from corruption have not been specifically regulated in legislation and implementing regulations. Efforts are made to improve and renew the Indonesia legal system regarding seizure and return of assets. And, through an agreement or cooperation both in mutual legal assistance and extradition regarding appropriation and return of assets are as the efforts to eradicate and prevent corruption in Indonesia.Keywords: Legal Policy, Crime, Corruption